Produção de bio-hidrogênio a partir da casca de arroz via processo de fermentação escura - Roman, Lizet Miriam Guevara (2021)
In the contemporary world, the growing global demand for energy, the reduction of non-renewable energy resources and the concern with the quality of the environment are noticeable. It is well known that the demand for hydrocarbons, which are the most energy source used today, exceeds the reserves forecast for the next decades. Furthermore, the environmental impact that their utilization has caused is responsible for global warming, destruction of the ozone layer, and disappearance of ecological systems in what some people call the sixth massive extinction. Thus, Bio-hydrogen (Bio-H2) can facilitate the decarbonization of certain carbon-emitting activities, as it is produced via dark fermentation, which is considered more viable, ecological and sustainable since it does not require an external energy source. Several types of lignocellulosic biomass can be used as a carbon source by microorganisms producing hydrogen (H2). In this sense, the objective of this work is to use rice husk (RH) and evaluate the production of H2 via the dark fermentation process under different types of inoculums. RH was characterized, prepared and submitted to the acid hydrolysis process with different concentrations of sulfuric acid and evaluated was performed based on the content of total sugars (TS) and at various concentrations of inhibitors. The selected hydrolyzate was then used as a substrate in the dark fermentation process, using two different types of sludge, anaerobic sludge granulation (ASG) and septic tank sludge (STS). The dark fermentation tests were carried out in a reactor with a substrate/inoculum ratio of 9 in the middle-temperature range of 35.8°C and neutral initial pH (6.5 - 7) and monitored for a period of 29 ± 1h approximately. The experimental condition that showed the highest total sugar recovery was the acid pretreatment to 1% v/v H2SO4. The recovery of TS in this condition was 201g kg RH-1, and inhibitor concentrations were less than the limit of quantification of 0.005 g L-1 for Furfural and 0.0005 g L-1 for 5-HMF, and the production and maximum yield of Bio-H2 were 5.37mL g RH-1 and 0.179 mL H2 h-1 g RH-1, respectively. Finally, it is concluded that the hydrolysate (1% v/v H2SO4) as substrate and ASG as inoculum exhibited adequate properties for the generation of Bio-H2 via the dark fermentation method, yielding promising results when compared to the literature.